Dynamics of BPJS Kesehatan Claims Resulting from Differences in the Interpretation of Healthcare Claims Verification: A Perspective on Legal Certainty and Justice - Neng Angie Rivera; Bram B Baan; Armansyah Armansyah (Jurnal Ragam Pengabdian, 2026)
Delayed and rejected claims remain persistent challenges in the implementation of Indonesia's National Health Insurance (JKN) program, particularly in inpatient healthcare services. One contributing factor is the difference in interpretation between the professional judgment of medical personnel and the administrative verification conducted by BPJS Kesehatan during the claims verification process. This study employed normative legal research using statutory and conceptual approaches to examine the implications of such differences from the perspectives of legal certainty and justice. The analysis was based on legislation, legal literature, and previous studies concerning the BPJS Kesehatan claims system, professional medical judgment, legal certainty, and justice. The findings demonstrate that differences in interpretation may arise in establishing diagnoses, supporting diagnostic examinations, medical coding, and determining claim eligibility. Consequently, healthcare services considered medically necessary based on professional judgment may not necessarily be recognized as eligible for reimbursement under the BPJS Kesehatan claims system. These differences contribute to delayed and rejected claims, creating legal uncertainty regarding healthcare facilities' entitlement to reimbursement while also raising concerns of justice due to the imbalance between administrative compliance and the legitimate interests of healthcare facilities. The study argues that a clearer mechanism for resolving differences in interpretation during claims verification is necessary to strengthen legal certainty and promote justice within the implementation of the National Health Insurance (JKN) program.